Diagnosis and Management of Choledochal Cyst in One Year-Old Baby: A Case Report - Riana Youri; Yusri Dianne Jurnalis; Jon Efendi (HM Publisher, 2023)
Background: Choledochal cysts (CC) are rare congenital anomalies of the biliary tract. The classic triad of jaundice, abdominal pain, and right upper quadrant mass are rare symptoms, mainly in children and adolescents. This study aimed to present the diagnosis and management of choledochal cyst cases in a baby girl. Case presentation: A 1-year-old girl, domiciled outside the city of Padang, was brought to the hospital by her parents with complaints of repeated vomiting for 1 day before being admitted to the hospital. This complaint has been accompanied by yellowish eyes and body, pale bowel movements, and dark brown urine since 3 months ago. The patient was never brought to the doctor for treatment. Since 1 month ago, the patient often feels pain in the abdomen and has a lump in the upper right abdomen. On the abdomen area, there was no distention, hepar was ¼-1/4 sharp edge, tenderness at the epicondrium area, no rebound tenderness, turgor was decreased, and no palpable mass. Abdominal ultrasonography presented a choledochal duct cyst with biliary obstruction. Abdominal CT scan with contrast revealed intrahepatic and extrahepatic biliaryectasis et causa suggestive of the choledochal cyst (Todani IVA) and hepatomegaly. The patient was consulted by the pediatric surgery division for further management and was advised to undergo surgery with the Roux En-y procedure. Follow-up after the patient underwent surgery showed clinical improvement. Symptoms of jaundice in the eyes and skin begin to decrease, as brownish stools and light brown urine. Conclusion: Surgical treatment with the Roux-en-Y procedure is the definitive treatment for choledochal cysts in this patient.